Pelatihan Pembuatan Kuis Interaktif Quizizz sebagai Media Evaluasi Pembelajaran Bahasa Arab dan Bahasa Inggris di Ma'had al-Jami'ah UIN Sayyid Ali Rahmatullah Tulungagung - Mardiyah, Tika; Ilmiah, Rikhlatul; Faidati, Ashima (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
Learning evaluation is an important component of the learning cycle that teachers must carry out. Through the evaluation, it was possible to know the achievement of the objectives of the student and the success of the learning process that has been carried out. Thus, as an attempt to equip Musyrifah Ma’had al-Jami’ah UIN Sayyid Ali Rahmatullah Tulungagung who served as a teacher of Arabic and English materials in Ma'had was required to respond to the development of technology, then training was needed to introduce the application that serves as an interesting and interactive evaluation media. The approach used in this dedication was Participation Action Research (PAR) which consists of initial mapping, building relationships with the community, participatory mappings, formulation of movement strategies, implementation of action for change, evaluation and reflection. From this training, the students be able to create interactive quizzes on quizizz while being able to apply them in the process of learning evaluation on Arabic and English language. Thus, the interactive quizizz training adds the skills of the students in designing learning evaluations interestingly and pleasantly